Effectiveness of Take and Give Method on Knowledge, Attitude, Adherence Iron Tablets in Pregnant Women - Milkah Ummi Nur Fadlilah; Triana Septianti Purwanto; Kharisma Kusumaningtyas; Uswatun Khasanah (Journal of Research in Midwifery and Healthcare, 2025)
Anemia in pregnancy remains a significant concern due to its potential adverse effects on both mother and fetus. This study aimed to assess the effectiveness of the Take and Give method in improving pregnant women's knowledge, attitude, and adherence to iron tablet consumption. A quasi-experimental design with a pre-test–post-test control group was employed, involving 60 pregnant women divided into intervention and control groups. The intervention group received education using the Take and Give method, while the control group used standard KIA books. Data were analyzed using the Wilcoxon and Mann-Whitney U tests. Data analysis results indicated that the 'Take and Give' method significantly influenced the increase in knowledge (p-value 0.000 < 0.05), attitude (p-value 0.000 < 0.05), and adherence (p-value 0.000 < 0.05). Furthermore, the 'Take and Give' method was more effective in improving pregnant women's knowledge, attitude, and adherence to iron tablet consumption compared to using KIA book media (knowledge p-value 0.003 < 0.05, attitude p-value 0.001 < 0.05, adherence p-value 0.049 < 0.05). The Take and Give method not only conveys information but also effectively shapes understanding and emotional responses affectively and evaluatively. This study recommends it as an innovative strategy to enhance understanding and positive behavioral changes in iron tablet consumption among pregnant women. The Take and Give method proved more effective than conventional methods in enhancing health behavior regarding iron supplementation in pregnancy.